Different and Unequal. About Legal Exclusion in the System of International Protection in Poland - Ołdak, Małgorzata (PRAWO i WIĘŹ, 2026)
This paper aims to demonstrate the impact of cultural differentiation related to the country of origin of refugees on their legal status and fundamental human rights and freedoms when entering Poland between 2021 and 2023. Due to the broad nature of the topic, the paper presents a selection of examples to illustrate the legal exclusion of certain groups seeking international protection in Poland. There is a demonstrable correlation between particular instances of human rights violations and the process of formulating and implementing legislation. Due to the multidimensionality of this issue, the paper is not intended to be exhaustive, but rather to outline a situational framework and background for more detailed analyses concerning systemic solutions for differentiating between refugees and migrants according to their country of origin when admitting them to a country and providing them with support.